Genomic Analysis of Serratia plymuthica MBSA-MJ1: A Plant Growth Promoting Rhizobacteria That Improves Water Stress Tolerance in Greenhouse Ornamentals - Nordstedt, Nathan P.; Jones, Michelle L. (Frontiers in Microbiology, 2021)
Water stress decreases the health and quality of horticulture crops by inhibiting photosynthesis, transpiration, and nutrient uptake. Application of plant growth promoting rhizobacteria can increase the growth, stress tolerance, and overall quality of field and greenhouse grown crops subjected to water stress. Here, we evaluated Serratia plymuthica MBSA-MJ1 for its ability to increase plant growth and quality of Petunia  hybrida (petunia), Impatiens walleriana (impatiens), and Viola  wittrockiana (pansy) plants recovering from severe water stress. Plants were treated weekly with inoculum of MBSA-MJ1, and plant growth and quality were evaluated two weeks after recovery from water stress. Application of S. plymuthica MBSA-MJ1 increased the visual quality and shoot biomass of petunia and impatiens and increased the flower number of petunia after recovery from water stress. In addition, in vitro characterizations showed that MBSA-MJ1 is a motile bacterium with moderate levels of antibiotic resistance that can withstand osmotic stress. Further, comprehensive genomic analyses identified genes putatively involved in bacterial osmotic and oxidative stress responses and the synthesis of osmoprotectants and vitamins that could potentially be involved in increasing plant water stress tolerance. This work provides a better understanding of potential mechanisms involved in beneficial plant-microbe interactions under abiotic stress using a novel Serratia plymuthica strain as a model.